Cash holdings in Germany and the demand for "German" banknotes: What role for cashless payments? - Nikolaus Bartzsch; Franz Seitz (Ostbayerische Technische Hochschule Amberg-Weiden (OTH), 2015)
This paper models the demand for banknotes issued in Germany. It highlights that all motives for holding banknotes are present in this case. Inter alia, special attention is paid to the role of card payments. For small and large denomination notes we are able to establish meaningful vector error correction models (VECM). The results suggest that the long-run demand for German small denomination notes is mainly driven by domestic transactions and demand from outside the euro area. The transaction motive in the rest of the euro area and non-cash payments are part of the short-term dynamics. The long-run demand for German large denomination notes is mainly driven by foreign demand both from the rest of the euro area and outside the EMU. The global financial crisis led to a one-time increase in the (real) demand for these notes. Our results are in line with estimates according to which the level and dynamics of banknote demand are largely determined by foreign demand. It was not possible to setup a VECM for medium denominations for which we resort to a singleequation approach. Card payments do not play any role for the medium and large denomination categories. – – Das vorliegende Papier modelliert die Nachfrage nach Euro-Banknoten, die von der Deutschen Bundesbank emittiert wurden. Dabei wird offensichtlich, dass alle Motive der Bargeldhaltung in diesem Fall relevant sind. Ein spezielles Augenmerk wird darauf gerichtet, welche Rolle bargeldlose Zahlungen in Form von Kartenzahlungen spielen. Für große und kleine Stückelungen gelingt es, aussagekräftige Vektorfehlerkorrekturmodelle (VECM) mir ökonomischem Gehalt aufzustellen. Langfristig wird die Nachfrage nach kleinen Stückelungen vor allem getrieben von inländischen Transaktionen und der Nachfrage außerhalb des Euro-Währungsgebietes. Das Transaktionsmotiv in den anderen Euro-Ländern und Kartenzahlungen treiben die Kurzfristdynamik. Die langfristige Nachfrage nach großen Stückelungen wird dagegen hauptsächlich von der Auslandsnachfrage innerhalb und außerhalb des Euro-Währungsgebiets getrieben. Die globale Finanzkrise führte dabei zu einem einmaligen Sprung in der realen Nachfrage nach diesen Noten. Für die mittleren Stückelungen konnte kein VECM aufgestellt werden. Deshalb musste auf einen Einzelgleichungsansatz zurückgegriffen werden. Kartenzahlungen beeinflussen weder die Nachfrage nach großen noch nach mittleren Stückelungen.
Keywords: C22; C32; E41; 330; banknotes; vector error correction; card payments